NEW MORPHOMETRIC ALGORITHMS OF IMAGE PROCESSING OF THE LYMPHANGIOGENESIS PATHOLOGY - M. V. Sprindzuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Authors describe in technical details a set of algorithms, developed and implemented for the goals of lymphangiogenesis and angiogenesis image processing with application for the comprehensive quantitative description, correlative statistics and tumoral expansion prognosis.